Effect of altitude and acetazolamide on postural control in healthy lowlanders 40 years of age or older. Randomized, placebo-controlled trial - Mutschler, Tim; Furian, Michael; Lichtblau, Mona; Buergin, Aline; Schneider, Simon R.; Appenzeller, Paula; Mayer, Laura; Muralt, Lara; Mademilov, Maamed; Abdyraeva, Ainura; Aidaralieva, Shoira; Muratbekova, Aibermet; et al. (Frontiers in Physiology, 2024)
Background: Hypoxia and old age impair postural control and may therefore enhance the risk of accidents. We investigated whether acetazolamide, the recommended drug for prevention of acute mountain sickness, may prevent altitude-induced deterioration of postural control in older persons.In this parallel-design trial, 95 healthy volunteers, 40 years of age or older, living <1000m, were randomized to preventive therapy with acetazolamide (375mg/d) or placebo starting 24hours before and during a 2-day sojourn at 3,100m. Instability of postural control was quantified by a balance platform with the center of pressure path length (COPL) as primary outcome while pulse oximetry (SpO2) was monitored. Effects of altitude and treatment on COPL were evaluated by ordered logistic regression. www.ClinicalTrials.gov NCT03536429.In participants taking placebo, ascent from 760m to 3,100m increased median COPL from 25.8cm to 27.6cm (odds ratio 3.80, 95%CI 2.53 to 5.70) and decreased SpO2 from 96% to 91% (odds ratio 0.0003, 95%CI 0.0002 to 0.0007); in participants taking acetazolamide, altitude ascent increased COPL from 24.6cm to 27.3cm (odds ratio 2.22, 95%CI 1.57 to 3.13), while SpO2 decreased from 96% to 93% (odds ratio 0.007, 95%CI 0.004 to 0.012). Altitudeinduced increases in COPL were smaller with acetazolamide vs. placebo (odds ratio 0.58, 95%CI 0.34 to 0.99) while drops in SpO2 were mitigated (odds ratio 19.2, 95%CI 9.9 to 37.6).In healthy individuals, 40 years of age or older, postural control was impaired after spending a night at 3,100m. The altitude-induced deterioration of postural control was mitigated by acetazolamide, most likely due to the associated improvement in oxygenation.